Reproductive and perinatal epidemiology - Louis, Germaine Buck.; Platt, Robert W. (New York ; Oxford : Oxford University Press, 2011)
A conceptual paradigm for reproductive and perinatal epidemiology is presented to define the field and its spectrum of possible study outcomes, followed by an overview of the relevant sensitive windows for study and substantive and methodologic issues underlying key study outcomes ranging from human fecundity to adverse birth outcomes.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Obstetrics; Perinatology; Epidemiology